Investigação de anticorpos contra Sarcocystis neurona e Sarcocystis cruzi em equinos - Antonello, A.M. (2015)
Sarcocystis neurona is the primary agent for Equine Protozoal Myeloencephalitis (EPM), important neurological disease characterized by behavior or muscular changes, that impairs animal performance and husbandry. Sarcocystis cruzi is a pathogen related to myositis in cattle. Although related the life cycles of the parasites are distinct. S. neurona has opossums (Didelphis spp.) and S. cruzi, dogs as definitive hosts. However, S. neurona and S. cruzi may undergo cross-reactivity in serological tests, interfering on results of EPM ante-mortem diagnostic tests. In the present study, serology of 189 mares was performed by indirect immunofluorescence antibody test, using antigens of S. neurona and S. cruzi in order to assess the exposure degree of animals to antigens. Analyzing the results, it was observed that most of the animals (84.13%) reacted with at least one protozoal species and the number of animals which showed antibodies against S. cruzi was greater than S. neurona (80.42% and 33.86%, respectively) and a third of seropositive animals reacted to antigens of both species.